An analysis of Population-Based Resource Allocation for health and social care in Ireland - Brendan Walsh; Leonie Hill (The Economic and Social Research Institute (ESRI), 2024)
The effectiveness of a healthcare system depends on its ability to distribute resources equitably and efficiently, aiming to improve the health and well-being of the population. This report, funded through a Department of Health research programme, examines the critical issue of healthcare resource allocation in Ireland. Its findings underscore the need for a resource allocation mechanism that can effectively address the varying healthcare demands across the country. The focus is on evaluating the current resource allocation mechanisms and exploring the potential of implementing population-based resource allocation (PBRA) mechanisms within proposed HSE Health Regions (HRs). PBRA mechanisms are employed successfully in other countries, and offer a structured approach to allocate healthcare resources based on population needs. These models consider various factors such as age, health status and socioeconomic conditions, ensuring a more equitable distribution of healthcare services. In Ireland, we have lacked a system-wide PBRA-type mechanism for making systematic health and social care resource allocation decisions. Within the Irish healthcare system, where challenges arise from demographic change and ongoing capacity constraints, PBRA mechanisms present an opportunity to enhance the efficiency and fairness of resource allocation. This proposed shift towards PBRA would also help to further the main goals of Sláintecare, by ensuring affordable universal healthcare for all, transferring more care into primary and community care settings, and developing a resource allocation mechanism to distribute funding, workforce and capacity to improve overall population health. The report aims to provide evidence to inform the establishment of PBRA in Ireland. It examines PBRA mechanisms within international systems and resource allocation and funding mechanisms in the Irish healthcare system. Lessons from this exercise are used to evaluate the Health Service Executive (HSE) HR restructuring and the PBRA formulae proposed by the Department of Health.
Keywords: 330